2011
DOI: 10.1177/0194599811425156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hearing Loss in Pediatric Patients with Down Syndrome

Abstract: Patients with DS present with a relatively high incidence of conductive hearing loss, MHL, and SNHL and a higher lost to follow-up rate compared to patients without DS. The authors were not able to diagnose SNHL within the 90-day period recommended by the Joint Committee on Infant Hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 15 publications
3
56
0
9
Order By: Relevance
“…A longitudinal study of 79 children with DS reported that OME was diagnosed in 93 % at age one, falling to 68 % by age 5 (Barr et al 2011). Similar findings have been reported in other series (Brooks et al 1972; Balkany et al 1979; Maurizi et al 1985; Dahle and McCollister 1986; Hassmann et al 1998; Kattan et al 2000; Mitchell et al 2003; Park et al 2011). COME may persist, and at least 10–20 % of adults with DS have a conductive hearing loss (Evenhuis et al 1992; Van Buggenhout et al 1999).…”
Section: Introductionsupporting
confidence: 87%
“…A longitudinal study of 79 children with DS reported that OME was diagnosed in 93 % at age one, falling to 68 % by age 5 (Barr et al 2011). Similar findings have been reported in other series (Brooks et al 1972; Balkany et al 1979; Maurizi et al 1985; Dahle and McCollister 1986; Hassmann et al 1998; Kattan et al 2000; Mitchell et al 2003; Park et al 2011). COME may persist, and at least 10–20 % of adults with DS have a conductive hearing loss (Evenhuis et al 1992; Van Buggenhout et al 1999).…”
Section: Introductionsupporting
confidence: 87%
“…Abnormal newborn hearing screen results in 22.8% is consistent with Utah DS neonate data [2]. The high rate of audiologic and hearing anomalies in our patients reinforces the DS Guideline recommendations for testing every 6 months until three years of age and then annually [29]. Our highest noncompliant rate of all guideline recommendations is audiology at 74%, which is disconcerting.…”
Section: Comorbiditiessupporting
confidence: 76%
“…Reports on the prevalence of hearing loss in DS vary considerably, but some degree of hearing loss has been noted in audiometric studies of children (Balkany, Downs, Jafek, & Krajicek, 1979; Park, Wilson, Stevens, Harward & Hohler, 2011; Roizen, Wolters, Nicol & Blondis, 1993; Shott, Joseph & Heithaus, 2001) and adults (Buchanan, 1990; Evenhuis, Van Zanten, Brocaar & Roerdinkholder, 1992). Survey studies show moderate prevalence of hearing impairment (Kumin, 2006; Schreve et al, 2009).…”
Section: Speech Sound Disorders (Table 2)mentioning
confidence: 99%